Sistem Informasi Helpdesk It Perum Peruri - Rahman Muharam; Feri Sulianta (Syntax Idea)
The purpose of this research is to study and analyze the effectiveness of the IT helpdesk system used to support IT services at Perum Peruri. Responses include services from the IT support department in solving problems related to computer hardware or the internet or company intranets which are very important to help work efficiency. To serve network requests and repair computers, laptops and printers is still done manually and this process takes a long time because it requires approval from superiors. In this case the monitoring of access requests, computer repairs and device network problems that are often complained about within 1 month is not properly recorded so that the process of evaluating these obstacles is solved. Methods In addition to interviews and observation systems, the authors conducted a literature review through information on research topics, scientific journals, books and references. For this reason, a helpdesk system for the IT Support section is needed which is computerized and can be accessed anywhere with an internet connection, so that existing problems can be resolved properly. And the process of tracking and reporting requests sent by users can be properly monitored and evaluated to find the right solution. Results, Describe the workflow of dispatchers in the helpdesk system. The dispatcher is in charge of sorting tickets or requests sent by users to the IT division, here the researcher divides into 3 sections, namely the infrastructure section, the helpdesk services section, and system maintenance. In conclusion, the information system makes it easier to organize data, speeds up the process of manual systems, can see tracking problems and find solutions, processing data can be more efficient and easy to access.